#### Answer

$x^{2}$+x-5

#### Work Step by Step

f(x)=x-6 and g(x)=$x^{2}$+1
(f+g)(x)=(x-6)+($x^{2}$+1)=
=$x^{2}$+x-5

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$x^{2}$+x-5

f(x)=x-6 and g(x)=$x^{2}$+1
(f+g)(x)=(x-6)+($x^{2}$+1)=
=$x^{2}$+x-5

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.